Promoting Sustainable Smallholder Aquaculture Productivity Through Landscape and Seascape Aquapark Models: A Case Study of Busia County, Kenya - Odende, Timothy; Ogello, Erick O.; Iteba, Jacob O.; Owori, Henrick; Outa, Nicholas; Obiero, Kevin O.; Munguti, Jonathan M.; Kyule, Domitila N.; Kimani, Shadrack; Osia, Moses M. (Frontiers in Sustainable Food Systems, 2022)
The dwindling capture fisheries has triggered an increase in Kenya’s annual fish demand deficit, currently estimated at 553,000 MT. The aquaculture potential in Kenya can bridge and surpass this deficit through adoption of proper policies. Kenya’s fish farming environment is however characterized by its highly fragmented production farms, which limit dynamism and technical change needed to commercialize aquaculture. The global trend in the commercialization of food production is through consolidation of farm lands. For example, most farms in the United States of America were also once small, but as a result of policy of land consolidation, the farm lands average 1,000 acres. Over the past decade, much of Sub-Saharan Africa nations are experiencing rise of 5 to 100 hectares except in Kenya, where the laws have exacerbated the situation. Amidst declining agricultural productivity, farm level efficiency and food security problems, land fragmentation is emerging as a key policy question in Kenya and is the single largest bottleneck, to aquaculture growth in Busia. Paradigm shift in the aquaculture development policy will enable aggregated production of fish under a fragmented land tenure. This paper discusses the need to remodel the current fragmented and uncoordinated cluster based small holder aquaculture development strategy by adopting a hybrid aquapark concept. In this concept the aggregated smallholder aquaparks are established and managed through specialized management service provision units and linked to adjacent small holder aquaculture production clusters with a community-based coordination and support framework. The paper further gives the application and socio-economic experiences of the pilot aquapark concept of aquaculture development in Busia County. The aquapark model coupled with deliberate establishment of aquaculture enabling infrastructure has enhanced efficiency, profitability and productivity of the aquaculture production. The realization of small holder community owned large-scale fish farms through aquaparks offers a window for dynamism and technical change necessary for commercialization of aquaculture under a fragmented land tenure system.